Only the raisins or all the pie? The implementation of the Varga-Neményi method in Finnish schools - Lampinen, Anni; Puumalainen, Kirsi (Gyermeknevelés Tudományos Folyóirat, 2014)
At the beginning of a course held at Helsinki University in 2000, Julianna Szendrei asked us, Finnish teachers the question: Who do we want to get to the finish line with – the few best pupils, „the average” or every single pupil, even if there will be some who will have to wear roller skates to get there. According to Eszter C. Neményi, who introduced all her courses with this, the teachers are driven by two kinds of love in their work: the love of children and the love of mathematics. Now, these thoughts are important and familiar to us, Finnish teachers as well. It is exactly the similar values, the similar view on teaching that aroused our interest: How do you teach here in Hungary? What novelties could we learn from you? This was the situation in 2000. Now we are here to tell you about Finnish mathematics teaching and about what we learnt from you, apart from the fact that our school culture is somewhat different from yours, how we are proceeding in the direction you set for us, and how we have formed the seven principles of Varga-Neményi to „our image”.